2014
DOI: 10.1080/09712119.2013.875902
|View full text |Cite
|
Sign up to set email alerts
|

Milk production and reproduction of dual-purpose cows with a restricted concentrate allowance and access to an association ofLeucaena leucocephalaandCynodon nlemfuensis

Abstract: The aim of the study was to evaluate the productive and reproductive performance of dual-purpose (DP) cows with a restricted concentrate allowance and access to a forage association of Leucaena (Leucaena leucocephala) and Stargrass (Cynodon nlemfuensis). Twenty-four multiparous Holstein × Zebu cows were used during the first 98 days postpartum. .97 ± 0.6, TL = 11.9 0.6) with a similar composition (P > 0.05). There were no differences (P > 0.05) between treatments for changes in live weight (CT −29.6 kg, LT −33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
5
6
1
1
Order By: Relevance
“…Content of ME was 1.9 Mcal·Kg -1 DM in C. plectostachyus, a value that is common in tropical grasses that have limited availability of energy (3) . Similar values were reported for this grass (18) . In turn, Leucaena provided 2.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Content of ME was 1.9 Mcal·Kg -1 DM in C. plectostachyus, a value that is common in tropical grasses that have limited availability of energy (3) . Similar values were reported for this grass (18) . In turn, Leucaena provided 2.…”
Section: Resultssupporting
confidence: 78%
“…These values are similar to those reported by Peniche-González et al (18) , who found an availability of 1692±766 and 1797±617.7 Kg DM·ha -1 for stargrass in dry and rainy seasons, respectively in an ISS in Mexico. On the other hand, L. leucocephala availability differed among grazing strips (82 to 939 Kg DM·ha -1 ).…”
Section: The Nutritional Balance Of Early Lactation Dairy Cows Grazinsupporting
confidence: 81%
See 1 more Smart Citation
“…Concerning to milk fat, protein, and lactose, similar results were found in a previous study with similar experimental conditions by Peniche-González et al (2014). Those authors suggested that the absence of difference in milk composition between treatments could have been due to a similar supply of milk precursors to the mammary gland of the cows.…”
Section: Milk Compositionsupporting
confidence: 76%
“…In this context, Peniche‐González et al. () attributed the lack of differences in milk content of fat, protein and lactose to similar supply of milk precursors to the mammary gland when the cows grazed in stargrass only or the association leucaena/stargrass. Milk pH values in the two systems appear to be normal for fresh milk (from 6.5 to 6.8) as reported by Fox and McSweeney ().…”
Section: Discussionmentioning
confidence: 99%